SELF ASSESSMENT INTEGRATED TRAINING AS AN EFFORT TO IMPROVE TEACHERS 'ABILITY IN DESIGNING TEST INSTRUMENTS - Sujatmi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by the fact that teachers did not design test instruments following the indicators and learning objectives, and teachers were unable to arrange instruments based on the level of difficulty and the use of language following the level of students’ understanding. This study aimed to improve the teachers’ ability to design test instruments through integrated self-assessment training activities. This research was school action research conducted on teachers of SDN 007 Pematang Ibul. The research subjects were 17 teachers. The data were collected through an observation sheet. The results showed that the teacher's ability to design the test instrument in cycle I was 71.78 with a good criterion, and it increased to 87.14 with a very good criterion in cycle II. Based on the results of this research, it could be concluded that integrated self-assessment training improved the teachers’ ability to design test instruments at SDN 007 Pematang Ibul.